## Trending News

### 6 Answers

- 1 decade agoFavorite Answer
First work inside the parentheses, and distribute.

5+ 3(1+2(2x-3))=6(x+5)

5+3((4x-6)+1)=5+3(4x-5)=5+12x-15=12x-10.

12x-10=6x+30. Next, try to isolate an x on one side. minus 6x+10 on both sides.

6x=40. Divide by 6.

x=40/6, or 20/3.

- Brittany<3Lv 61 decade ago
5+3[1+2(2x-3)]=6(x+5)

5+3[1+4x-6]=6(x+5) first step is mult. 2 by (2x-3)

5+3[4x-5]=6(x+5) add the 1 to the now 4x-6

5+12x-15=6(x+5) Mult. 4x-6 by 3

12x-10=6x+30 Add the 5 to -15, so it becomes a -10

6x-10=30 Subtract 6x from both sides

6x=40 Add 10 to the other side, so one side will have a variable and the other a reg. number

x=40/6=20/3 Divide 40 by 6, and when you reduce, you get 20/3..then plug the answer back in as x to check if it's right...if both sides= the same # it's right...if not SOL and try again

Yay it's right!

Okay with the calc. or manually

if you substitute x with 20/3,

you get 70 on both sides

= ]

Always remember PEMDAS (please excuse my dear aunt sally aka parentheses, exponent, multiplication, division, addition, subtraction...the order of operations)

- Anonymous1 decade ago
5+3[1+2(2x-3)]=6(x+5)

8[3(2x-3)]=6x+30

8(6x-9)=6x+30

48x-72=6x+30

+72 +72

48x=6x+102'

-6x

42x=102

divide 42

x approximately =23.5

Source(s): my brain - How do you think about the answers? You can sign in to vote the answer.
- 1 decade ago
5+3[1+2(2x-3)]=6(x+5)

8[3(-1)=6(x+5)

24=6(x+5)

24=6x+30

-30

_________

24=6x+0

24/6=4

Source(s): me and my brain and my big sis